Exploration of trust in participatory health research partnerships across two timepoints: a network approach - Meghan Gilfoyle; Anne MacFarlane; Jon Salsberg; Miriam McCarthy; Padraig MacCarron (BMJ Open)
Background The value of a participatory approach to the generation of evidence for health and social services from a moral, methodological and policy level continues to gain recognition globally. Trust is a crucial mechanism in the participatory health research (PHR) process and is strongly influenced by context. However, gaps remain in conceptualising and operationalising trust over time in PHR partnerships.Objective This case study seeks to address these gaps by exploring the evolution of trust multidimensionally across two timepoints.Setting and participants Participants in a PHR project called the Public and Patient Involvement (PPI) Ignite Network in Ireland (n=57 (T1); n=56 (T2)) were invited to complete a network survey at two timepoints. The PPI Ignite Network had local and national partners.Network measures Several core social network measures were calculated at both timepoints to characterise the differences between trust dimensions and between local and national partners.Results Subtle changes were observed across most network measures over the two timepoints. While there was a slight decrease in the number of connections for each trust dimension throughout the PPI Ignite Network, connections that were consistently nominated in both timepoints increased slightly. Some trust dimensions, such as vulnerability and integrity, were more similar, while others, like integrity and shared values, visions and goals, differed greatly, where national partners consistently received more incoming connections compared with local partners.Conclusion These findings (1) provide empirical support for using social network analysis to operationalise trust comprehensively and multidimensionally over time in a participatory partnership, (2) offer nuanced insights into the trust development process within the PPI Ignite Network and (3) enhance our understanding of trust in the community-based participatory research model.